2012
DOI: 10.1007/s10120-012-0178-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of clinical outcomes between laparoscopy-assisted proximal gastrectomy (LAPG) and laparoscopy-assisted total gastrectomy (LATG) for proximal gastric cancer

Abstract: Background The choice of surgical strategy for patients with proximal gastric cancer is controversial. The purpose of this study was to assess the feasibility, safety, and surgical and functional outcomes of laparoscopy-assisted proximal gastrectomy (LAPG) and laparoscopy-assisted total gastrectomy (LATG). Methods Between June 2003 and December 2009, 131 patients with proximal gastric cancer underwent LAPG (n = 50) or LATG (n = 81) at Seoul National University Bundang Hospital. We reviewed their medical and su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
113
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(129 citation statements)
references
References 21 publications
4
113
5
Order By: Relevance
“…In recent years, a tendency to increasing numbers of proximal gastric cancers has been reported, and early detection and potentially curative operations by PG for upper-third gastric cancers have been increasing [24,25]. For outcome measures with * higher score indicates better condition; for outcome measures without * higher score indicates worse condition If b is positive, the score of the outcome measure of the patients belonging to the category in brackets is higher in cases when the factor is a nominal scale, and the score of outcome measure of the patients with larger values is higher in cases when the factor is a numeral scale QOL comparison of PG and TG 413 In this study, the effect of tumor progression was removed by constraining patient selection to those with pathologic Stage IA/IB disease, and it is thought that accurate QOL comparison between operative procedures is possible under these circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, a tendency to increasing numbers of proximal gastric cancers has been reported, and early detection and potentially curative operations by PG for upper-third gastric cancers have been increasing [24,25]. For outcome measures with * higher score indicates better condition; for outcome measures without * higher score indicates worse condition If b is positive, the score of the outcome measure of the patients belonging to the category in brackets is higher in cases when the factor is a nominal scale, and the score of outcome measure of the patients with larger values is higher in cases when the factor is a numeral scale QOL comparison of PG and TG 413 In this study, the effect of tumor progression was removed by constraining patient selection to those with pathologic Stage IA/IB disease, and it is thought that accurate QOL comparison between operative procedures is possible under these circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore difficult to assess the course of postoperative recovery in retrospective studies. In most studies, mortality was low and acceptable, with no significant differences between different patient groups [18][19][20][21][22][23][24].…”
Section: Postoperative Recoverymentioning
confidence: 98%
“…Although ten LTGs were included in this study, this was not regarded as the first report, because of its small sample size and because the results were collected by a questionnaire. Since LTG was first reported as a technical note in 1999 [26], some further studies have been reported [18][19][20][21][22][23][24]. Of these, the highest number of publications has been from Japan (n = 50), followed by Korea (n = 42; see Fig.…”
Section: Annual Publicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this issue of Gastric Cancer, Ahn et al [1] present a series of 131 patients with early-stage proximal gastric cancer who underwent laparoscopic resection, either in the form of laparoscopy-assisted total gastrectomy (LATG) or that of laparoscopy-assisted proximal gastrectomy (LAPG). The comparison of these two minimally invasive techniques with assessment of multiple early and late measures of outcomes is intriguing, and although not being based on a randomized trial deserves careful recognition and analysis.…”
mentioning
confidence: 99%